Bolívar Echeverría: on Existencialism - Anangonó Rosero, Gersón; Naranjo Navas, Cristian Paúl (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2020)
The present study reviews the most important existentialist schools of thought as an introduction to understand the intellectual approach of the Ecuadorian philosopher Bolívar Vinicio Echeverría Andrade about existentialism. Echeverría was one of the most important thinkers of the philosophy for Latin America. The work covers the approach of Echeverría on the existentialism of the twentieth century, through the inscription of his thought in “The Humanism of Existentialism”.